L’Hospital’s Rule and Exponents

Curious about expressions like \( x^x \)? In this post, I’ll explain how you can use L’Hospital’s Rule in unexpected ways to solve this problem:

$$ \lim_{x \to 0^+} x^x = 1 $$

Note: \( x \to 0^+ \) signifies that \( x \) approaches \( 0 \) from the right.

It turns out that the above problem is related to my previous post, which describes the following problem:

$$ \lim_{x \to 0^+} x \ln(x) = 0 $$

To see how that is so, consider \( x^x \). In general,

$$ x = e^{\ln(x)} $$

That is because the exponential function and \( \ln(x) \) cancel each other out.

So, I can write:

$$x^x = (e^{\ln(x)})^x $$

It turns out that

$$ (e^{\ln(x)})^x = e^{x \ln(x)}. $$

So,

$$ x^x = (e^{\ln(x)})^x = e^{x \ln(x)}. $$

Now, we can solve the problem. Since \( x^x = e^{x \ln(x)} \),

$$ \lim_{x \to 0^+} x^x = \lim_{x \to 0^+} e^{x \ln(x)}. $$

It turns out that

$$ \lim_{x \to 0^+} e^{x \ln(x)} = e^A $$

where

$$A = \lim_{x \to 0^+} x \ln(x). $$

This is where L’Hospital’s Rule comes in. As explained in my previous post, this rule can be used to calculate the following:

$$ \lim_{x \to 0^+} x \ln(x) = 0 $$

So, \( A = 0 \). Recall that any number to the power of zero is one. So as

$$ \lim_{x \to 0^+} e^{x \ln(x)} = e^A $$

We have

$$ \lim_{x \to 0^+} e^{x \ln(x)} = e^0 = 1 \,. $$

So as

$$ \lim_{x \to 0^+} x^x = \lim_{x \to 0^+} e^{x \ln(x)}, $$

$$ \lim_{x \to 0^+} x^x = 1 $$

which is the answer we’re looking for.

Comments

No comments yet. Why don’t you start the discussion?

    Leave a Reply

    Your email address will not be published. Required fields are marked *